#CanadaPerforms: How it Came to Be and What We Learned About Building Virtual Communities - Chan, Kevin (Critical Studies in Improvisation / Études critiques en improvisation)

(untitled) (University of Guelph College of Arts, 2021)
Kevin Chan is Director of Public Policy, Canada for Facebook. In this piece, he describes the origins of the #CanadaPerforms series, a partnership between Facebook Canada and the National Arts Centre that presented over seven hundred livestreamed musical performances by Canadian musicians during the pandemic.